2019
DOI: 10.1038/s41421-019-0080-3
|View full text |Cite
|
Sign up to set email alerts
|

Regrowth-delay body as a bacterial subcellular structure marking multidrug-tolerant persisters

Abstract: Bacteria have long been recognized to be capable of entering a phenotypically non-growing persister state, in which the cells exhibit an extended regrowth lag and a multidrug tolerance, thus posing a great challenge in treating infectious diseases. Owing to their non-inheritability, low abundance of existence, lack of metabolic activities, and high heterogeneity, properties of persisters remain poorly understood. Here, we report our accidental discovery of a subcellular structure that we term the regrowth-dela… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 59 publications
6
68
0
1
Order By: Relevance
“…In yeast, research has shown protein aggregation to be reversible and protect proteins from stresses [54,56]. Recent studies in E. coli suggested potential roles of protein aggregates in stress responses, although it is still unclear whether aggregates are dissolved or passed down to offspring, or if both could happen depending on the situations [72,73]. Based on our results, protein aggregation might protect some of the A. baumannii proteome from damage during desiccation and provide functional proteins for recovery once rehydrated.…”
Section: Discussionsupporting
confidence: 54%
“…In yeast, research has shown protein aggregation to be reversible and protect proteins from stresses [54,56]. Recent studies in E. coli suggested potential roles of protein aggregates in stress responses, although it is still unclear whether aggregates are dissolved or passed down to offspring, or if both could happen depending on the situations [72,73]. Based on our results, protein aggregation might protect some of the A. baumannii proteome from damage during desiccation and provide functional proteins for recovery once rehydrated.…”
Section: Discussionsupporting
confidence: 54%
“…Protein photocrosslinking coupled with scarless genome-targeted site-directed mutagenesis reveal that the "inserted" state of the ATP synthase ε-subunit could be detected in living bacterial cells overnight cultured in common LB rich medium 5 In an attempt to find out whether the "inserted" state of the ε-subunit of the ATP synthase is actually formed in living cells, we focused on the interactions involving the C-terminal helix (i.e., the α-helix at the C-terminal end) of the ε-subunit. For this purpose, we made use of the photoactivatable unnatural amino acid p-benzoyl-L-phenylalanine (Bpa), which after being genetically incorporated into a target protein and upon UV irradiation would be able to effectively mediate covalent photocrosslinking with the interacting proteins in cells living under any particular experimental conditions (Chin et al, 2002;Zhang et al, 2011;Fu et al, 2013;Wang et al, 2016;Yu et al, 2019;.…”
Section: Resultsmentioning
confidence: 99%
“…S1b), in which the functioning of the ATP synthase was indispensable for the cells to grow. In addition, for an effective introduction of Bpa into target proteins, here we made use of the E. coli bacterial strain LY928 that we generated by inserting the optimized DNA sequences encoding the orthogonal Bpa-tRNA synthetase and the orthogonal tRNA Bpa at a specifically selected site on the genomic DNA causing hardly any disruption on cellular activities (Wang et al, 2016;Yu et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations